2009
DOI: 10.1128/aem.00054-09
|View full text |Cite
|
Sign up to set email alerts
|

Rhodobacter capsulatus Catalyzes Light-Dependent Fe(II) Oxidation under Anaerobic Conditions as a Potential Detoxification Mechanism

Abstract: Diverse bacteria are known to oxidize millimolar concentrations of ferrous iron [Fe(II)] under anaerobic conditions, both phototrophically and chemotrophically. Yet whether they can do this under conditions that are relevant to natural systems is understood less well. In this study, we tested how light, Fe(II) speciation, pH, and salinity affected the rate of Fe(II) oxidation by Rhodobacter capsulatus SB1003. Although R. capsulatus cannot grow photoautotrophically on Fe(II), it oxidizes Fe(II) at rates compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 46 publications
0
51
1
Order By: Relevance
“…1b). Similar concentrations of Fe(II) are inhibitory to the growth of Rhodobacter capsulatus grown under humic acid-oxidizing phototrophic conditions (19). A lag was also observed in NDFO cultures of A. ebreus containing higher Fe(II) concentrations (8 to 10 mM) (see Fig.…”
Section: Evidence Against An Inducible Fe(ii) Oxidoreductase Inmentioning
confidence: 60%
See 1 more Smart Citation
“…1b). Similar concentrations of Fe(II) are inhibitory to the growth of Rhodobacter capsulatus grown under humic acid-oxidizing phototrophic conditions (19). A lag was also observed in NDFO cultures of A. ebreus containing higher Fe(II) concentrations (8 to 10 mM) (see Fig.…”
Section: Evidence Against An Inducible Fe(ii) Oxidoreductase Inmentioning
confidence: 60%
“…Some studies have demonstrated that Fe(II) at low concentrations is toxic to anaerobic bacteria such as anoxygenic phototrophs (19) or streptococci (20). Several possibilities for anaerobic Fe(II) toxicity include inhibition of the F-ATPase (20), binding to membranes (21), disruption of protein stability or replacement of active-site metal cofactors (22), and oxidation and precipitation of insoluble Fe(III) on cellular components to impair nutrient uptake (13).…”
mentioning
confidence: 99%
“…3c and d) for cells preincubated with Fe(II)-EDTA, showing that Fe(II) exposure does not result in antibiotic resistance. In addition, Fe(II) oxidation has been suggested as a potential detoxification mechanism in the photoheterotrophic, Fe(II)-oxidizing strain Rhodobacter capsulatus SB1003 (32). However, upregulation of such a detoxification response seems unlikely in our studies as we have no evidence of either Fe(II)-or Fe(III)-EDTA toxicity (2).…”
mentioning
confidence: 66%
“…Fe 2ϩ is known to be toxic due to the formation of oxygen radicals in the Fenton reaction under oxic conditions (64). There are only a few studies concerning the toxicity of Fe 2ϩ under anoxic conditions (65,66). Some nitrate-reducing Fe(II)-oxidizing strains are not able to grow on dissolved Fe(II) but instead require chelated Fe(II), for example, Paracoccus ferrooxidans (41) and Pseudogulbenkiania strain MAI-1 (67), and it was suggested by those authors that this was due to Fe 2ϩ toxicity.…”
Section: Discussionmentioning
confidence: 99%